Comparing barriers to breastfeeding success in the first month for non-overweight and overweight women - Kimberley M. Mallan; Lynne A. Daniels; Rebecca Byrne; Susan J. de Jersey (BMC, 2018)
Abstract Background Women who enter pregnancy overweight or obese tend to have poorer breastfeeding outcomes compared to non-overweight women. Women's experiences of specific breastfeeding-related problems and reasons for use of formula have not been systematically investigated according to pre-pregnancy BMI. The aim of this study was to compare self-reported breastfeeding problems in non-overweight and overweight women and identify the main reasons for use of infant formula during the first month postpartum. Methods The present study involved a cross-sectional secondary analysis of data collected as part of a hospital-based longitudinal study of women that commenced in pregnancy (~ 16 weeks). At ~ 4 months postpartum Australian women (N = 477) self-reported breastfeeding problems and reasons for use of infant formula during the first month postpartum. Pre-pregnancy BMI was calculated based on self-reported pre-pregnancy weight and measured height. Binary logistic regression analyses were used to compare pre-pregnancy weight status groups ("non-overweight" [BMI < 25 km/m2] and "overweight" [BMI ≥25 km/m2]) on self-reported breastfeeding problems and reasons for use of infant formula. Analyses were adjusted for covariates that differed between groups (P < .1). Results Frequency of self-reported breastfeeding problems was similar across weight status groups. "Not enough milk" was the predominant reason for giving infant formula. Overweight women were more likely than non-overweight women to agree that infant formula was as good as breastmilk. Conclusions Overall it does not appear that overweight women are more likely to experience a range of specific breastfeeding problems in the first months compared to non-overweight women. However, the severity and duration of the problems needs to be examined. Breastfeeding interventions need to addresses concerns around milk supply as these are common and are likely to be of universal benefit however overweight women in particular may benefit from guidance regarding the benefits of breastfeeding for both themselves and their infants.